Author Correction: Endogenous FGF21-signaling controls paradoxical obesity resistance of UCP1-deficient mice - Susanne Keipert (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-22119-x